Assessment of the knowledge and attitudes on osteoporosis among female students at the College of Applied Medical Sciences, Taif City, Saudi Arabia - Gharib, Amal Fathy; Ismail, Khadiga; Farghaly, Asmaa; Hagag, Howaida; Alosimi, Samia; Alamri, Kholod (Jour Med Resh and Health Sci, 2019)
Background: Osteoporosis is an increasing chronic health problem that could lead to mortality and a bad quality of life. Awareness about osteoporosis and the conditions that contribute to it is of major benefit and an important health challenge. Purpose: This research was conducted to assess the awareness and attitudes about the osteoporosis among female medical students at the College of Applied Medical Sciences, Taif University. Materials and methods: Design of an osteoporosis questionnaire. One hundred questionnaires were distributed to faculty female students to evaluate their knowledge of osteoporosis. Questionnaires were gathered, findings were tabulated and SPSS was used to properly assess the information. Results: There was a high level of knowledge on osteoporosis associated with the period of study at the College of Applied Medical Sciences. The fourth-year nursing students had a high level of knowledge on osteoporosis (66 percent) followed by third-year laboratory students (64 percent) and followed by second-year students of radiology (48 percent). Conclusion: We concluded from this study that raising the knowledge about osteoporosis and its risk factors is an important and effective tool in preventing osteoporosis.